IMPLEMENTASI PENDEKATAN TARL PADA PEMBELAJARAN IPAS MATERI BENTANG ALAM UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDN DUKUH KUPANG 1 SURABAYA - Devika Arfiana Farazeni; Diah Yovita Suryarini; Mawan Dwiyanto (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to improve the learning outcomes of third-grade elementary school students in Natural and Social Sciences (IPAS) on the topic of Landscapes by implementing the Teaching at the Right Level (TaRL) approach. This approach involves grouping students according to their cognitive ability levels, allowing the learning process to be tailored to the specific needs of each group. The research employed the Classroom Action Research (CAR) model developed by Kemmis and McTaggart, conducted over two cycles. Data were collected through observations, interviews, and learning outcome tests. The findings indicate that the TaRL approach effectively enhanced student learning outcomes, as demonstrated by an increase in mastery learning from 46% in the pre-cycle to 68% in the first cycle, and further to 86% in the second cycle. These results suggest that differentiated instruction based on cognitive development levels can significantly support students in better understanding IPAS material.